Job Burnout: A Case of Public Organizations in Pakistan - Younus, Sohail; Azeem, Muhammad; Mirza, Farhan (Pakistan Journal of Humanities and Social Sciences, 2023)
Emotional labor has a robust foundation in public organizations, especially concerning healthcare workers. For this reason, the present study explores the degree to which emotional labor tactics result in burnout for representatives directly dealing with patients.This study aims to find the association among dimensions of emotional labor and burnout with the mediating mechanism of stress. Emotional labor scales were operationalized to measure the emotional work, type of acting, and negatively or positively displayed rules. The research contains quantitative data collected using a set of questions administered to 107 nurse practitioners and medical professionals regarding staff from Government Hospitals in Pakistan. A significant correlation was located between the variables and meaningful relationships among different constructs, and job stress partly mediates the relationship. This survey will help to examine the consequences of such components for burnout and job stress.